Embracing Briquette Fuel in Nigeria: Challenges, Implications and Way-Out: - Gidigbi, Joshua; Sani, Z; Muhammad, A.B.; Olarewaju, A.B.; Eneche, J (Jurnal Bio-Geo Material Dan Energi, 2025)
Energy is crucial to critical development of any nation. It is a major determinant of economy power. Unfortunately, fossil fuel which has served as a major means of energy remain unsustainable and has detrimental effect on the environment. Renewable source of energy such as biomass promising a better replacement since it is ecofriendly and sourced from unlimited feedstock. Briquette is one of the alternative sources of energy derived from biomass. It has the potency of replacing wood fuel with good heating value and substantial heating time. It is eco-friendly and sustainable. it is majorly produced from waste residue of agricultural process and production which make it more susceptible as an alternative source of heating energy in sub-Sahara Africa, especially, Nigeria which was referred to as agricultural nation. Nigeria has many crop residues including groundnut- shells and straw; rice- straw and husk, maize-Stalk, cob and husk; cassava- stalks and peelings, soybean- straw and pods, sugar cane-bagasse and tops/leaves, cotton-stalk, millet- straw, sorghum-straw, and cowpea's shell which could serve as a good raw material for briquette production. Despite the huge availability of feedstock, manpower and technical how, briquette formulation merely exists in the nation. The commercialization of briquette in the country has failed woefully. Thus, a need for comprehensive studies on the missing links on why briquette does not thrive like other Africa nations such as Uganda and Kenya. This study reviewed; challenges; implications and way out associated with briquette technology in Nigeria.